Reducing fluoroscopy time during cardioverter-defibrillator implantation, performed with considering of myocardium perfusion scintigraphy results in patients with coronary artery disease - T. A. Atabekov; R. E. Batalov; S. N. Krivolapov; M. S. Khlynin; S. I. Sazonova; A. D. Shvarzman; G. Zh. Suranova; S. V. Popov (Российский кардиологический журнал, 2018)
Aim. Implantable cardioverterdefibrillator (ICD) implantation technique optimization in patients with coronary artery disease (CAD) in order to reduce fluoroscopy time and total radiation dose to staff.Material and methods. Patients with CAD and indications for the ICD implantation were examined. Patients were divided into two groups. In first group before ICD implantation, patients underwent cardiac 99mTcmethoxyisobutylisonitrile scintigraphy for right ventricle wall perfusion disorders assessment. In this group defibrillating lead was implanted to the septal position, if the perfusion disorders were in the apical segments, and to the apical position, if perfusion disorders were in the septal segment. In second group lead was implanted using conventional approach. Fluoroscopy duration and radiation dose were compared.Results. There were 58 patients (male52, female6, age64,5±8,5 years) enrolled. The first group consisted of 27 (46,5%) patients. For 13 (48,1%) patient ICD was implanted for primary, and 14 (51,9%) one for secondary sudden cardiac death (SCD) prevention. In 14 (51,9%) cases in this group defibrillating lead was implanted to the apical and in 13 (48,1%) — to the septal position. The 2nd group consisted of 31 (53,5%) patients. For 13 (41,9%) patient ICD was implanted for primary, and 18 (58,1%) one for secondary SCD prevention. In 15 (48,3%) cases in this group defibrillating lead was implanted to the apical and in 16 (51,7%) — to the septal position. There were significant differences between groups in terms of fluoroscopy duration  — 85,5±28,1 and 131,6±53,5 sec (р=0,0001) and radiation dose — 0,14±0,07 and 0,21±0,08 (p=0,0004) mSv, respectively.Conclusion. Assessment of right ventricular perfusion before ICD implantation reduce fluoroscopy time and total radiation exposure to staff.